Pengaruh Motivasi Dan Lingkungan Sosial Terhadap Minat Berwirausaha (Studi kasus Pada Mahasiswa Fakultas Ekonomi Universitas Sumatera Barat) - Mexano Hans Gery (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research is entitled The Influence of Motivation and the Social Environment on Interest in Entrepreneurship in Students of the Faculty of Economics at the University of West Sumatra. This research is motivated by the need for economics students to be able to create their own jobs with the ability or motivation support provided by their surroundings, without having to wait for the relevant agencies to open job vacancy. This research uses a quantitative type of research. The data taken was primary data by distributing questionnaires to students at the Faculty of Health Sciences at the University of West Sumatra. This research carried out research instrument tests, classical assumption tests, hypothesis tests using SPSS version 21. The research results stated that looking at the test results that had been carried out proved that both variables had a significant effect partially or simultaneously, and it could also be seen that the Adjusted R Square was 0.372 or amounting to 37.2%. This means that the variable interest in entrepreneurship is influenced by motivation and the social environment and the remaining 62.8% is influenced by other variables outside of this research variable.